Control of Asian soybean rust with mancozeb, a multi-site fungicide - Silva,Luís Henrique Carregal Pereira da (2015)
An experiment conducted in the field the action of mancozeb, a fungicide of multi-site action was tested, to control soybean rust caused by Phakopsora pachyrhizi. Its performance was compared to that of the mixture cyproconazole (DMI) + azoxystrobin (QoI). The soybean cultivar NA 7337 RR was used with a population of 400,000 plants/ha cultivated in 20m2 plots. Treatments consisted of mancozeb levels (1.5 and 2.0 kg/ha) applied four, six and eight times. The DMI + QoI mixture was applied three times at 0.3 L/ha + Nimbus. Rust severity was assessed six times in the plots and data were integrated as the area under the disease progress curve (AUDPC). The plots were harvested and grain yield was expressed as kg/ha. Data on AUDPC and yield were subjected to analysis of variance and means compared according to Turkey's test (p = 0.005). Treatments with mancozeb were superior to DMI + QoI mixture both for rust control and grain yield. Four applications of 2.0 k/ha mancozeb were more efficient than three applications of the mixture used as standard. Mancozeb has the potential to be added to fungicide mixtures in the establishment of soybean rust anti-resistance strategy.